Ratio Legis Of The Principle Of Sovereignty In The Regulation Of Plantation Business As A Settlement Of Land Disputes/Conflicts - Hairan Hairan; Imam Koesahyono; Tunggul Anshori Setia Negara; Bambang Sugiri (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Plantation businesses have existed since the past, especially growing rapidly during the Dutch colonial era. The Dutch Colonial Government then made several laws and regulations regarding the regulation of land . Currently, plantations are under the umbrella of the Plantation Law and UUCK. In terms of Legis ratio, the inclusion of "the principle of sovereignty in the Plantation Law actually increases the legitimacy of Plantation Companies to take MHA Ulayat land by force and arbitrarily. The principle of sovereignty in the Plantation Law is not in line with the state's right to control all natural resources in Indonesia's territorial territory. Land disputes and conflicts leading to plantation land are an indirect implication of the Principle of Sovereignty, which is systematically formalized in the Plantation Law to strengthen the position of Plantation Companies, even though it reduces the sacred value of a nation and State, which is given through the principle of sovereignty to Plantation Companies